On the interaction of DNA nanostructures with lipid bilayers - Journot, C (2017)
Much of our knowledge of cellular biology arises from direct observation of active cellular functions. Tools and techniques have steadily developed over the past several hundreds of years to aid in our understanding and control of the nanoworld and are referred to as nanotechnologies. In the context of nanotechnology, DNA is not used as a carrier for genetic information (as it is in cell), but as a construction material. DNA offers unprecedented control over the construction of simplified biomimetic models for the study of biological processes. This thesis first introduces and defines the field of DNA nanotechnology, with particular emphasis on the interaction of snthetic DNA nanostructures with biological membranes. Inspired by the protein clathrin, three-fold symmetric DNA tile made of eight, short DNA strands and capable of polymerising is described and studied, with the aim to interact with and controllably bend a membrane bilayer. This structure presented challenges during construction so an enhanced three-armed DNA structure built with DNA origami was designed. The succesful assembly of a rigid and functionalisable nanostructure is described. This origami structure was polymerised into large constructs in solution and on a supported lipid membrane. The shape of the structure was modulated to vary its curvature and apply a bending force to a lipid vesicle when anchored to it. Following the conclusion of this study, we present the construction of a small, unique DNA structure for enhanced electron microscopy imaging in cell lysate. This project is part of a developing technique to couple the interaction specificity of dyes in super-resolution microscopy and the high-resolution output of electron microscopy. Finally, the optimisation procedures and recommendations for TEM imaging of samples of DNA origami and lipid structures are discussed.